Analisis Metode Support Vector Machine (SVM) Dan Random Forest Terhadap Perilaku Dan Prestasi Siswa Berbasis Kurikulum Merdeka Di SMK Negeri 1 Stabat - Ibrahim, I; Iqbal, Muhammad; Khairul, K (STIKOM Tunas Bangsa Pematangsiantar, 2025)
This study analyzes the influence of student behavior on academic achievement at SMKN 1 Stabat, using a quantitative approach with simple linear regression analysis on 245 tenth-grade students. The results show a positive and significant influence, with a coefficient of determination (R²) value of 0.272, indicating that student behavior contributes 27.2% to academic achievement. Discipline and responsibility are the most influential behavioral aspects, where students with high discipline tend to be more consistent in learning and completing assignments. The implications of this study highlight the importance of character building and positive behavior development within the school environment through collaboration among teachers, parents, and school administrators. Although not the sole determinant of success, good behavior such as discipline, responsibility, and active learning has been proven to enhance student learning outcomes. Therefore, efforts to improve the quality of education should consider not only cognitive aspects but also the development of constructive behavior through guidance programs and the strengthening of intrinsic motivation.